Bridging the evidence-practice gap for people with gout - Mark D. Russell; James B. Galloway (Exploration of Musculoskeletal Diseases)
Gout is a common and disabling form of arthritis. Despite widely available, highly effective, urate-lowering therapies, such as allopurinol, studies continue to demonstrate poor care for individuals with gout in healthcare systems worldwide. In this commentary, we highlight strategies that can be utilised to overcome real-world barriers to optimal gout care, including allied health professional input, patient and clinician education, self-management strategies, and electronic health record solutions.